Phylogenetic beta diversity of angiosperms in North America. Issue 10 (27th May 2013) - Qian, Hong; Swenson, Nathan G.; Zhang, Jinlong
Abstract: Aim: Ecologists have generally agreed that beta diversity is a key component of global patterns of species richness. Incorporating phylogenetic information into the study of beta diversity allows researchers to identify the degree to which the shared evolutionary histories of species explain ecological patterns observed today. For example, phylogenetic analyses can determine whether closely related species tend to occupy similar positions along broad climatic gradients and whether this explains the compositional turnover along these gradients. Despite the promise of phylogenetic beta diversity analyses, few continental‐scale investigations exist. Here, we quantify the phylogenetic beta diversity and taxonomic beta diversity of the angiosperm flora across North America. We relate these metrics to one another and to geographical and environmental distances to uncover the phylogenetic signal underlying species compositional turnover. Location: North America. Method: Seventy‐one regional floras were used and assigned into five latitudinal zones and two longitudinal bands. The Sørensen index and PhyloSor index were used to quantify taxonomic similarity and phylogenetic similarity, respectively, between floras, and were related to geographical and environmental distances. Results: Phylogenetic similarity between floras is strongly correlated with taxonomic similarity, is higher in eastern North America than in western North America, and increases strikingly with latitude. Geographical and environmental distances together explained on average about 76% of the variation in phylogenetic beta diversity with environmental distance explaining more variation in phylogenetic similarity in three of the four latitudinal bands examined. Main conclusions: The results show that phylogenetic beta diversity is consistently lower than taxonomic beta diversity, which suggests that the spatial turnover of species in the study system is predominantly the spatial turnover of closely related species and not distantly related species. Thus, the turnover of angiosperm floras in North America is best explained by small divergences along environmental axes for closely related species and a gradual turnover of lineages through space.